Leadership styles among faculty academics in a Malaysian university: a preliminary insight - Zulkifly, Nurul Afiqah; Ismail, Ismi Arif; Md Rami, Ahmad Aizuddin; Che Nawi, Nur Raihan (Human Resource Management Academic Research Society, 2022)
Universities in Malaysia are putting a never-ending effort to ensure academics’ growth through strong leadership. Leadership program such as mentor-mentee is being re-highlighted to help faculties prosper. However, the success of such effort highly depends on leadership style that is not inclined towards hierarchy and bureaucracy. Therefore, this paper aims to investigate the dynamics of leadership styles (transformational leadership, transactional leadership, and laissez-faire leadership) exhibited by academics in a faculty of a Malaysian university. This paper offers a descriptive result describing the most practiced leadership styles among the academics. The results indicate that most academics exhibit high level of both transformational and transactional leadership behaviours with the latter being the most frequently used leadership style.